2019
DOI: 10.5114/wo.2019.89243
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and acceptance of the disease in patients with lung cancer during palliative chemotherapy

Abstract: IntroductionAn important part of the therapeutic process of patients with lung cancer undergoing palliative chemotherapy is to assess their mental well-being. Evaluation of the sense of coherence and acceptance of the disease, which reflects the degree of adaptation of the patient to live with the disease, provides information on this topic.ObjectiveThe primary objective was to assess the level of sense of coherence and acceptance of the disease in patients with lung cancer during palliative chemotherapy as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
1
Order By: Relevance
“…The AIS score in the examined sample of lung cancer patients was 32.23 points, which means quite high level of its acceptance. However, these values are significantly higher than those of patients treated for lung cancer included in the works of other authors, who scored 27.21 points [11], 27.10 points [18] and 23.17 points. [23].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The AIS score in the examined sample of lung cancer patients was 32.23 points, which means quite high level of its acceptance. However, these values are significantly higher than those of patients treated for lung cancer included in the works of other authors, who scored 27.21 points [11], 27.10 points [18] and 23.17 points. [23].…”
Section: Discussioncontrasting
confidence: 56%
“…It is therefore very important for the patient to meet with a surgeon who will operate on him/her before the planned surgery. Moreover, the level of knowledge of the medical personnel about this subject and/or its improper transfer also has a significant impact on adaptation to the disease [11]. All this may lead to a number of psychological complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in treatment options and survival rates affects only subgroups of patients; still, the vast majority suffer from a high psychological burden, which can lead to reduced quality of life and distress. Anxious thoughts about the course of the disease are among the stress-related symptoms experienced by cancer patients [ 1 ]. Unaddressed psychological problems in clinical practice can have a negative impact on therapy outcome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that in adulthood, SOC remains relatively stable, and even after radical life events, only temporary fluctuations occur. It has been shown that SOC is unaffected by age, gender, education, and place of residence (Nowicki et al, 2019). Other research has provided evidence that neither race nor education affect SOC among patients with cancer and chronic diseases (Bruscia et al, 2008).…”
Section: Introductionmentioning
confidence: 99%